Everglades Invasive Reptile and Amphibian Monitoring Program: Summary of the First Five Years - Rebecca G. Harvey; Michael R. Rochford; Jennifer Ketterlin Eckles; Edward F. Metzger; Jennifer Nestler; Frank J. Mazzotti (EDIS, 2017)
Lists the objectives, activities, and accomplishments of the Everglades Invasive Reptile and Amphibian Monitoring Program over its first five years and describes some ways Floridians and visitors to the state can help with the effort.